PROSPECTS OF DIGITALIZATION IN EDUCATION - Qutbiddinov Otabek Zayniddin o’g’li (Western European Studies, 2026)
This article examines the prospects of digitalization in education and its transformative impact on modern learning systems. In recent years, rapid advancements in information and communication technologies (ICT) have reshaped traditional educational models, shifting from teacher-centered approaches to more student-centered and technology-driven environments. Digital tools such as learning management systems (LMS), virtual classrooms, artificial intelligence (AI), cloud computing, big data analytics, and mobile applications have significantly enhanced the accessibility and efficiency of education.
Keywords: Digitalization; Digital Education; E-learning; Online Learning